Student and Instructor Ratings in Geographic Information Systems: A Comparative Analysis - Emilio Ortega; Belén Martín; Sergio González-Ávila (MDPI AG, 2024)
Geographic information system (GIS) education empowers engineering students to make informed decisions, integrate comprehensive data, and communicate effectively through maps and visualizations. In GIS education, it is common to employ problem-based learning, which can benefit from the advantages of peer assessment methods. Among the benefits of peer assessment are the enhancement of students' capacity for analysis and synthesis, improvement in organizational and professional communication skills, and the development of critical judgement. However, a consequence of its application is that there may be variation in students' final grades, with no consensus in the literature on this matter. This paper explores the extent to which the application of peer ratings among students can modify student grades in the field of GIS education. This was achieved by conducting an experiment in which undergraduate engineering students assessed two problem-based learning activities carried out by their peers in two different basic GIS courses. The ratings obtained after the peer assessment were compared with the grades given by the instructors. The results allowed us to debate whether the teaching benefits of this strategy compensate for the differences between the students' grades and those given by instructors. Although no clear pattern was found in the mean ratings awarded by the two groups of evaluators, the results show that student engagement in peer assessment was high. This experience has demonstrated that the assessments of the two groups complement each other and allow students to gain a better understanding of their ratings and how to improve their skills.